Skinfolds compressibility and calliper's time response in male athletes - Bini, A (2018)
Introduction: The body skinfolds compressibility is an individual characteristic determined by tissues properties. Compressibility could affect the skinfold thicknesses inducing error in the assessment of subcutaneous adipose tissue and in the estimation of body composition. Objectives: This study aims to firstly describe the time behaviour of eight body skinfolds' physical response to the skinfold calliper pressure during measurement. Methods: Using a digital skinfold calliper that gathers 60 measurements per second, the dynamic response of height skinfolds to pressure was characterized in 36 adult male athletes. To assess the skinfolds compressibility, two points were defined L and H: the S-L corresponds to the lowest value within the 120 measurement the time when it was obtained was defined as T-L. The T-H corresponds to the first moment where the 110% of of the value S-L was measured. The equations of the average of each skinfold as a function of time were obtained from a non-linear fitting. Results: Skinfold compressibility varied according subjects (p< 0.05). Significant differences were found among skinfold sites within S-H, S-L, T-H and T-L, confirming that each skinfold compressibility is different from the other, even within a homogeneous study group. Biceps was the first skinfold to reach the minimum thickness value (T-L= 1.08 +/- 0.38s), while iliac crest was the last one (T-L= 1.63 +/- 0.27s). Given the very good fits that were obtained for all skinfolds (R-2 >= 0.997), it was postulated that the skinfold thickness y changes with time t according to the equation: y = y0 + a/(b + t(n)). Conclusions: Inter and intraindividual skinfolds' variation in compressibility was documented, supporting a reduction in protocolled time during evaluations.